(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Some people may wonder if emotions have anything to do with language or believe that emotion cannot be the subject of serious scientific research. In fact, this has been a common belief for many years, even among linguists and other scientists. But, fortunately, this is yesterday's news. Today's news is that emotions matter in every scientific work, field, and linguistics in particular, as it is a key factor not only in understanding human nature, but also in understanding human language and communication.